The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.1097/nen.0b013e3181d0f7d5
|View full text |Cite
|
Sign up to set email alerts
|

Brody Disease: Insights Into Biochemical Features of SERCA1 and Identification of a Novel Mutation

Abstract: Brody disease is an inherited disorder of skeletal muscle function characterized by increasing impairment of relaxation during exercise. The autosomal recessive form can be caused by mutations in the ATP2A1 gene, which encodes for the sarcoplasmic/endoplasmic reticulum Ca-ATPase 1 (SERCA1) protein. We studied 2 siblings affected by Brody disease. The patients complained of exercise-induced delay of muscle relaxation and stiffness since childhood and had gene analysis of ATP2A1. Morphologic and biochemical stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 20 publications
0
41
0
3
Order By: Relevance
“…This was done on transverse muscle sections using fluorescence method with antibodies to SERCA1 (1:500; Santa Cruz Biotechnology, Santa Cruz, CA) and SERCA2 (1:100; Santa Cruz Biotechnology, Santa Cruz, CA). We compared the results with controls including biopsies of vastus lateralis muscle from subjects who were found to be free of muscle disease [14,19].…”
Section: Serca1 and Serca2 Immunohistochemical Stainingmentioning
confidence: 99%
See 1 more Smart Citation
“…This was done on transverse muscle sections using fluorescence method with antibodies to SERCA1 (1:500; Santa Cruz Biotechnology, Santa Cruz, CA) and SERCA2 (1:100; Santa Cruz Biotechnology, Santa Cruz, CA). We compared the results with controls including biopsies of vastus lateralis muscle from subjects who were found to be free of muscle disease [14,19].…”
Section: Serca1 and Serca2 Immunohistochemical Stainingmentioning
confidence: 99%
“…We reviewed all publications cited by Pubmed on 'Brody disease', 'Brody syndrome' or 'Brody myopathy' since the initial description in 1969 by Brody [2] until 2010 and the references of these articles, and selected all patients in whom clinical data were available (n = 32; Supplementary Table 1) [2,4,5,[7][8][9][10][11][12][13][14]. We classified them as literature ("L") cases, numbered them chronologically, and screened the case descriptions for clinical key features of Brody disease.…”
Section: Review Of Literature Cases and Selection Of Literature (L) Cmentioning
confidence: 99%
“…Functional studies on muscle samples from humans with Brody's disease have demonstrated that some patients exhibit reduced levels of SERCA1 protein content [105,106], while in other cases the levels of SERCA1 protein are unaltered, but there is a significant reduction (up to 80%) in the Ca 2+ pumping activity both in homogenates of muscle samples and in myotubes explanted from patients [99,106,107]. Chianina cattle pseudomyotonia, a disease similar to Brody's disease affecting cattle, is caused by the homozygous ATP2A1 p.R164H mutation [108].…”
Section: Brody's Diseasementioning
confidence: 99%
“…Five of these patients (BD2 and BS2-BS5) have been previously described at clinical, morphological, biochemical and genetic level; one (BD2) was a compound heterozygous with two in-frame deletions occurring in exon 3 (Leu65) and in exon 15 (Glu606) of ATP2A1 [12] while in the remaining four patients (BS2-BS5) no pathogenic mutations were detected in the gene (S3, S2, S8 and S5 in Voermans et al [7]). …”
Section: Muscle Biopsiesmentioning
confidence: 99%
“…Ultrastructural abnormalities include increased number of membranous bodies within sarcoplasmic reticulum (SR) vesicles, enlargement of lateral cisternae with proliferation of the tubular SR elements and presence of swollen mitochondria [11,12].…”
Section: Introductionmentioning
confidence: 99%